(untitled) (El Hilo de la Fabula, 2018)
This research aims to verify the existence of a dispute field between human and social sciences, exact, health, nature; as well as the hierarchy identification in UFRRJ and the opportunities given to their students. The methodology was centered in qualitative and descriptive nature. Semi–structured interviews with students, teachers and coordinators were made. The purpose is to understand the process related to the Program. The conclusion of this research is the hierarchies are presents at UFRRJ, being the same attested by his own agents, when evidence they are established in different aspects in academic life.